CONSTRUCTION OF SOCIAL IDENTITY THROUGH SLANG OF THE YOUNG GENERATION OF JAPAN AND MANADO: A SOCIOLINGUISTIC PERSPECTIVE IN A COMPARATIVE LITERATURE STUDY - Dina Chatrina Magdalena Rottie (SOSIOEDUKASI, 2026)
Youth slang is a sociolinguistic phenomenon marking social identity construction in the digital era. This research analyzes social identity construction through Japanese youth slang (wakamono kotoba) and Manado slang in comparative sociolinguistic perspective. The research objectives are to analyze linguistic characteristics, identify social identity construction mechanisms, and compare identity construction patterns between both cultural contexts. The research method employs qualitative approach with library research, analyzing 2021-2025 literature through content analysis. Results show wakamono kotoba has 13 complex formation processes influenced by four Japanese writing systems, while Manado slang is more flexible through blending, clipping, and regional language integration. Identity construction mechanism occurs through three layers (personal, enactment, communal) with convergence and divergence strategies on digital platforms. Similarities in both contexts include group solidarity functions and linguistic creativity. Significant differences are identified in extremely rapid Japanese slang change cycles and stronger secrecy functions, while Indonesia experiences regional language shift with foreign language dominance on social media. The research suggests developing longitudinal studies, educational approaches recognizing slang creativity, and regional language revitalization strategies relevant to youth digital ecology